KOMODIFIKASI AGAMA PADA KESENIAN HADRAH KUNTULAN BANYUWANGI - Arif, Muhamad; Nisa, Jakiatin (Sosio-Didaktika: Social Science Education Journal, 2018)
This study aims to obtain an overview of the factors of commodification of religion in the Hadrah Kuntulan in Rogojampi District. Through qualitative research, there are several findings about the commodification factors of religion in the Hadrah Kuntulan as follows. First, internally there are concerns if the monotonous Hadrah will be abandoned by the community so that they cannot play a role as Islamic da'wah media. Second, externally, there are demands from the public to see the performance of Hadrah that is more interesting and entertaining. These two factors have encouraged the artists to modify the Burdah into an interesting Islamic art by adopting several elements of regional art, resulting in dynamic Hadrah Kuntulan and even evolved into performing arts. Although the messages of da'wah remain the main characteristics that have never been abandoned, the Hadrah Kuntulan began to change with strong commercial nuances.